Analisa Kualitatif Formalin pada Sampel Ikan Asin di Pasar Sederhana Kota Bandung - Lusi Noorrela; Indra Putra Munggaran (Food Scientia : Journal of Food Science and Technology, 2021)
Salted fish is one of the most nutritious foods consumed in Indonesia but it is very prone tospoilage. Due to the speed of decomposition of salted fish, many traders use formaldehyde asa preservative for salted fish. Regulation of the Minister of Health of the Republic ofIndonesia Number 1168 / Menkes / PER / X / 1999 states that formalin is a preservative thatis prohibited from being used as a food preservative because it can cause damage to thedigestive tract, liver and lungs, and can even cause cancer. The purpose of this study was toidentify the formaldehyde content in salted fish sold in the Sederhana Market in Bandung.This research was conducted by taking samples at the Sederhana Market in Bandung.Qualitative analysis of formaldehyde was carried out at the Chemical Testing Laboratory ofBalai Besar Pengawas Obat dan Makanan in Bandung in October 2020. Formalinidentification of 25 fish samples was done colorimetrically using the MERCK test kit. Basedon the grouping of salted fish, positive results were obtained by 20% for Salted Anchoviesand 100% for Salted Cucut Fish, while Salted Kapas Fish, Salted Squid, and Salted SepatFish did not contain formaldehyde. The conclusion of this study is that 24% of salted fishtaken from the Bandung Sederhana Market was positive for formaldehyde. The group thatcontains the most formalin is Salted Cucut Dish.